Level of Utilization And User Satisfaction of Cold Chain Facility of Fishing Port Nusantara Ternate - Surahman, Surahman; Karman, Amirul; Kaidati, Bahar; Riani, Syeha Filna; Hi. Iksan, Kusdi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
The purpose of this study is to describe the existing conditions of cold chain facilities (ice factories, cold storage, and air blast freezers) and to analyze the utilization and satisfaction of these cold chain facilities at the Indonesian fishing port, Ternate City, North Maluku Province. The research has been carried out at the fishing port of the archipelago of Ternate, for one month, from March to April 2022. The research method used is a case study. Cold chain facilities at PPN Ternate City consist of: 1). an ice factory with a capacity of 10 tons/day; 2). four ABF units, consisting of 1 unit with a capacity of 4 tons/12 hours in damaged condition, 2 units each with a capacity of 2 tons/12 in good condition used, 1 unit with a capacity of 3 tons/12 hours in good condition used, and 3 units with a capacity of 2.5 tons / 12 hours in good condition both used and ; 3). three cold storage units, each with a production capacity of 100 tons, 60 tons, and 50 tons, are in good condition. The utilization rate of ABF and cold storage has exceeded the optimal limit, while the ice factory has not been optimal. All users expressed dissatisfaction with the service of the ABF facility and very dissatisfied with the service of the cold storage facility, while the ice factory facility was satisfied.